Error rate in the decisions of elite futsal referees in the context of their position on the pitch - Kresta, J.; Colak, M.; Carboch, J.; Skopek, M.; Cihlar, D.; Tirpak, J. (Studia Sportiva, 2022)
One of the primary requirements for a futsal referee is the minimum of incorrect decisions in a match. An important starting point for the possibility of the correct decision of the referee is his position on the court when deciding. The aim of the thesis is to find out whether the error rate of the futsal referee changes when assessing game situations (leading to a direct free kick) in connection with his position. The research group consisted of referees of the 1st futsal league in the Czech Republic (n = 15); average age 39.4 (SD = 6.2). A total of 685 game situations were assessed from 42 matches in the 2020/21 and 2021/22 seasons. The methods of work were: indirect observation of video recordings, notation analysis, expert assessment of game situations by an expert group (n = 5). Results: the error rate in the decisions of referees is 7%; inadequate positions detected 3%; A statistically significant relationship was found between the degree of error rate in the referees' decisions and the quality of the position (rs = .32, p < .001) but no material significance was found. We recommend a more detailed research solution to this issue.